2012
DOI: 10.5935/0104-7795.20120038
|View full text |Cite
|
Sign up to set email alerts
|

Addressing functional activities and the influence of environmental factors in post-stroke hemiparetic patients before and after physical therapy

Abstract: Stroke is the leading cause of neurological disability and hemiparesis is its most common sequelae. The physical and functional limitations combined with the influence of environmental factors directly affect an individual's functionally. For an effective neurological rehabilitation, it is essential that physiotherapists know the patient's functional profile in order to plan the treatment to meet his/her real needs. Objective: To analyze the functional activities and influence of environmental factors in posts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Such conditions result from brain lesions and are sequelae (hemiplegia and hemiparesis), which impair (at different intensities) the person's daily life. Another study (21) showed hemiparesis as the most common stroke sequelae and, also, associates the physical and functional limitations to environmental factors (it highlights that they directly affect the functionality of the subjects), which imposes difficulties in participating in tasks and daily life activities. Check Table 3 for the limitations in activities and the restriction to participation.…”
Section: Discussionmentioning
confidence: 99%
“…Such conditions result from brain lesions and are sequelae (hemiplegia and hemiparesis), which impair (at different intensities) the person's daily life. Another study (21) showed hemiparesis as the most common stroke sequelae and, also, associates the physical and functional limitations to environmental factors (it highlights that they directly affect the functionality of the subjects), which imposes difficulties in participating in tasks and daily life activities. Check Table 3 for the limitations in activities and the restriction to participation.…”
Section: Discussionmentioning
confidence: 99%
“…Os achados do presente estudo corroboram com os achados de outros autores que tem estudado as repercussões de atividades terapêuticas para a melhora na funcionalidade de sujeitos pós AVE 27,28,29 , relatando melhoras após diferentes protocolos de intervenção, como o uso da dança, treino em esteira e mesmo a terapia convencional.…”
Section: Discussionunclassified